2007
DOI: 10.1017/s0022112006003788
|View full text |Cite
|
Sign up to set email alerts
|

Spatial signatures of retrograde spanwise vortices in wall turbulence

Abstract: The spatial signatures of retrograde spanwise vortices in wall turbulence are assessed from particle-image velocimetry measurements in the streamwise-wall-normal plane of a zero-pressure-gradient turbulent boundary layer at Re τ ≡ u * δ/ν = 2350. The present results suggest that a proportion of retrograde spanwise vortices have a welldefined spatial relationship with neighbouring prograde vortices. Two-point crosscorrelations and conditionally averaged velocity fields given a retrograde vortex reveal that such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 16 publications
2
40
0
Order By: Relevance
“…is the root-mean-square value of Λ ci at wall-normal position y and λ ci is the imaginary part of the complex eigenvalue of the two-dimensional velocity gradient tensor (Zhou et al 1999, Adrian et al 2000a. Similar methods were used by Natrajan et al (2007) and Herpin et al (2010) That is, spanwise vortex filaments crossing the x-y plane always have spanwise vorticity, but some portions of the regions containing spanwise vorticity do not qualify as filaments. Thus, spanwise vorticity is due to both spanwise vortex filaments and non-filamentary structures.…”
Section: Properties Of Net Forcementioning
confidence: 99%
See 1 more Smart Citation
“…is the root-mean-square value of Λ ci at wall-normal position y and λ ci is the imaginary part of the complex eigenvalue of the two-dimensional velocity gradient tensor (Zhou et al 1999, Adrian et al 2000a. Similar methods were used by Natrajan et al (2007) and Herpin et al (2010) That is, spanwise vortex filaments crossing the x-y plane always have spanwise vorticity, but some portions of the regions containing spanwise vorticity do not qualify as filaments. Thus, spanwise vorticity is due to both spanwise vortex filaments and non-filamentary structures.…”
Section: Properties Of Net Forcementioning
confidence: 99%
“…The backward induced motion makes a hairpin vortex convect more slowly than the surrounding flow and the upward induced motion lifts it away from the wall. Since the origion of retrograde spanwise vortex filaments in wall turbulence is still not totally clear (Natrajan et al 2007), proper interpretation of their convection velocity is not attempted in the present study. In contrast to net force, the spanwise vortex filaments contribute little to the Reynolds stress.…”
Section: Convection Velocitymentioning
confidence: 99%
“…Wu & Christensen (2006a) found that these counterclockwise-rotating retrograde spanwise vortices have their largest populations toward the outer edge of the log layer where they generally occur in close proximity to prograde spanwise vortices. Natrajan et al (2007) found that these spatially-coincident pairs of prograde and retrograde spanwise vortices may be linked to the measurement plane slicing through the shoulders of omega-shaped hairpin-like structures. While figures 43 and 44 illustrate the imprint of the spatial organization present in flow over both smooth and RF1 surface conditions within the x -y plane, these structures also leave a definitive imprint within velocity fields acquired in the streamwise-spanwise (x -z) plane.…”
Section: Introductionmentioning
confidence: 92%
“…More recently, Klewicki & Hirschi (2004) reported observations of hairpin vortices and retrograde structures clustered in the neighborhood of intense near-wall shear layers, with the influence of retrograde structures increasing with Reynolds number. Finally, Natrajan et al (2007) performed a detailed investigation of the spatial signatures of outer-layer retrograde spanwise vortices, particularly their propensity to occur spatially-coincident with prograde cores, and reported that such patterns are also consistent with slicing through omega-shaped hairpin structures. It should be noted that the existence of ring-like vortices is not inconsistent with the hairpin-vortex model as the origin of ring-like structures in wall turbulence has been related to the pinch-off and reconnection of the legs of existing hairpin structures (Moin et al, 1986;Smith et al, 1991;Bake et al, 2002, for example).…”
Section: "Outside the Roughness (Or Viscous) Sublayer The Turbulent mentioning
confidence: 98%
See 1 more Smart Citation